2018
DOI: 10.2147/cmar.s187559
|View full text |Cite
|
Sign up to set email alerts
|

Association of markers of systemic and local inflammation with prognosis of patients with rectal cancer who received neoadjuvant radiotherapy

Abstract: PurposeThe inflammatory status of patients with cancer appears to affect cancer progression and patient prognosis. We examined the characteristics of cancer-associated systemic and local inflammation and its impact on the overall survival (OS) of patients with locally advanced rectal cancer (LARC) who received neoadjuvant radiotherapy (nRT).Patients and methodsSeventy-six consecutive LARC patients who received nRT from February 2012 to September 2015 were retrospectively analyzed. The peripheral neutrophil-to-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Analyses included PFS in 15 studies, [10,1730] DFS in 11 studies, [16,17,3137] DMFS in 8 studies, [19,23,27,30,38,39] DSS in 1 study, [23] and pathologic CR in 2 studies on preoperative CCRT. [25,40] The median NLR cut-off value was 3.1 (range 1.9–5.0). ROC curves were used to estimate the optimal NLR cut-off value in 14 studies.…”
Section: Resultsmentioning
confidence: 99%
“…Analyses included PFS in 15 studies, [10,1730] DFS in 11 studies, [16,17,3137] DMFS in 8 studies, [19,23,27,30,38,39] DSS in 1 study, [23] and pathologic CR in 2 studies on preoperative CCRT. [25,40] The median NLR cut-off value was 3.1 (range 1.9–5.0). ROC curves were used to estimate the optimal NLR cut-off value in 14 studies.…”
Section: Resultsmentioning
confidence: 99%
“…The NLR was defined as the absolute neutrophil count divided by the absolute lymphocyte count within 2 weeks before the initial treatment. [4][5][6][7][8][9][10][11][12][13][14] The cutoff value calculated from the ROC curve, mean, tertile, or median in previous studies varied from 1.98-5; 4-11 thus, the standard cutoff value remains unknown. In the current study, the cutoff value was defined as the mean value of the NLR.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3] The peripheral neutrophil-to-lymphocyte ratio (NLR) is a well-known inflammatory marker. Several authors have previously reported that a high NLR is significantly associated with poor survival in solid cancers, [4][5][6][7][8][9][10][11][12][13][14] including head and neck squamous cell carcinoma and breast cancer. However, whether the NLR affects prognosis in patients with parotid cancer remains unknown; therefore, the current study aimed to clarify this question.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that markers of systemic inflammation could be useful biomarkers for the diagnosis of many cancers. As far as we know, there were several retrospective analyses that investigated the relationship between PLR, neutrophil‐lymphocyte ratio (NLR), and albumin‐globulin ratio (AGR) in the prognosis of rectal cancer . But rarely have studies assessed the diagnosis role of these hematological parameters in rectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…As far as we know, there were several retrospective analyses that investigated the relationship between PLR, neutrophil-lymphocyte ratio (NLR), and albumin-globulin ratio (AGR) in the prognosis of rectal cancer. 11,15,16 But rarely have studies assessed the diagnosis role of these hematological parameters in rectal cancer. Therefore, we intend to investigate the role of PLR, hemoglobin-platelet ratio (HPR), and CEA, which were used alone or in combination, in early screenings and diagnoses of rectal cancer.…”
mentioning
confidence: 99%